Binding of p53 and its core domain to supercoiled DNA - Palecek, E; Brázdová, M; Brázda, V; Palecek, J; Billová, S; Subramaniam, V; Jovin, T M (European journal of biochemistry, 2001)
We have compared the binding of human full-length p53 protein (p53; expressed in bacteria and insects) and its isolated core domain (p53CD, amino acids 94-312; expressed in bacteria) to negatively supercoiled (sc) DNA using gel electrophoresis and immunoblotting. Significant differences were observed; p53CD produced a relatively small and continuous retardation of scDNA, in contrast to the ladder of distinct bands formed by p53 in agarose gels. The ladder produced by full-length protein expressed in bacteria (p53b) was similar to that observed earlier with protein expressed in insect cells (p53i). Competition between scDNAs and their linearized (lin) forms showed a preference for scDNAs by both p53 and p53CD, but the ratios characterizing the distribution of the protein between sc and lin pBluescript DNAs were substantially higher for p53 (sc/lin > 60 in p53b) than for p53CD (sc/lin approximately 4). Strong binding of p53 to scDNA lacking the p53 consensus sequence may represent a new p53-binding mode, which we tentatively denote supercoil-selective (SCS) binding. This binding requires both the C-terminal domain and the core domain. Targets of this binding may include: (a) DNA segments defined both by the nucleotide sequence and local topology, and/or (b) strand crossings and/or bending. The binding preference of p53CD for scDNA may be due to the known nonspecific binding to internal single-stranded regions in scDNA (absent in relaxed DNA molecules) and/or to SCS binding albeit with reduced affinity due to the absence of contributions from other p53 domains.
Keywords: Electrophoresis, Agar Gel; Baculoviridae; elektroforéza v agarovém gelu; vysoká teplota; Hot Temperature; Protein Binding; nádorový supresorový protein p53; Dose-Response Relationship, Drug; vazebná místa; plazmidy; Binding Sites; DNA; superhelikální DNA; kompetitivní vazba; konformace nukleové kyseliny; vazba proteinů; Binding, Competitive; Nucleic Acid Conformation; vztah mezi dávkou a účinkem léčiva; Plasmids; terciární struktura proteinů; DNA, Superhelical; Protein Structure, Tertiary; Tumor Suppressor Protein p53